Secure System Design and Trustable Computing - Chang, Chip-Hong; Potkonjak, Miodrag (Springer International Publishing : Imprint: Springer, 2016)
This book provides the foundations for understanding hardware security and trust, which have become major concerns for national security over the past decade.  Coverage includes issues related to security and trust in a variety of electronic devices and systems related to the security of hardware, firmware and software, spanning system applications, online transactions, and networking services.  This serves as an invaluable reference to the state-of-the-art research that is of critical significance to the security of, and trust in, modern society's microelectronic-supported infrastructures.